Concurrent, predictive validity and reliability of the algorithm in the stages of change for rapid HIV testing - Aranda-Ibarra, Jesús Ramón (2023)
Objective. To evaluate the concurrent, predictive validity and reliability of an algorithm designed to determine the stage of change for HIV testing. Methods. A cross-sectional, correlational, two-stage study was conducted. The first, with 300 young university students, to evaluate the concurrent and predictive criterion validity with variables such as self-efficacy, knowledge about HIV testing and risk perception, measured with instruments that present Cronbach's a between ,73 and ,93. The second in 75 migrants, considered as at-risk population (n = 75), to assess reliability by means of a test-retest. Results. The predominant stages of change for HIV testing in both samples were precontemplation and contemplation. The stages of change correlated with two of the concurrent variables of self-efficacy and knowledge (p < ,01). The regression model was significant (F [3,296] = 53.68, p < ,001), predicting 35 % of the variance in stages of change. A significant intraclass correlation was found in the test-retest (ICC=,97, CI [,952-,981], p < ,01). Conclusions. The stage-of-change algorithm for HIV testing presents acceptable psychometric characteristics of concurrent and predictive validity, as well as high temporal stability of the measure, so its use in practice is recommended.